A systematic review and meta-analysis of low intensity CBT for psychosis. (April 2016) - Hazell, Cassie M.; Hayward, Mark; Cavanagh, Kate; Strauss, Clara
Abstract: Sixteen sessions of individual cognitive behavior therapy for people with psychosis (CBTp) is recommended. However, access to CBTp is poor, so the potential of low intensity CBTp (fewer than 16 sessions of face-to-face contact) is being explored. A systematic review and meta-analysis was conducted of 10 controlled trials evaluating low intensity CBTp. Significant between-group effects were found on the primary outcome, symptoms of psychosis, at post-intervention ( d = − 0.46, 95% CI: − 0.06, − 0.86) and follow-up ( d = − 0.40, 95% CI: − 0.06, − 0.74). Study quality did not moderate post-intervention psychosis outcomes, nor did contact time/number of sessions or therapy format (individual versus group). Between-group effects on secondary outcomes (depression, anxiety and functioning) were not significant at post-intervention, but became significant at follow-up for depression and functioning outcomes (but not for anxiety). Overall, findings suggest that low intensity CBTp shows promise with effect sizes comparable to those found in meta-analyses of CBTp more broadly. We suggest that low intensity CBTp could help widen access. Future research is called for to identify mechanisms of change and to ascertain moderators of outcome so that low intensity CBTp targets key mechanisms (so that scarce therapy time is used effectively) and so that interventions offered are matched to patient need. Highlights: 16 + sessions of CBT for psychosis is recommended, but this is not widely available. A meta-analysis of low intensity (i.e. fewer sessions) CBT for psychosis is reported. Small–medium between-group effects were found for psychosis symptoms at post-therapy. Small–medium between-group effects for psychosis symptoms remained at follow-up. Effects were not moderated by study quality or therapist contact or therapy format.